A chiral pool approach for asymmetric syntheses of (−)-antrocin, (+)-asperolide C, and (−)-trans-ozic acid. Issue 84 (9th September 2016) - Li, Fu-Zhuo; Li, Shuang; Zhang, Peng-Peng; Huang, Zhi-Hui; Zhang, Wei-Bin; Gong, Jianxian; Yang, Zhen
Abstract : Ozonolysis of aromatic abietanes is used to create the important intermediates, resulting in a simple, concise, and asymmetric synthesis of three terpenes. Abstract : Ozonolysis of aromatic abietane (+)-carnosic acid (4 ) is used to create an important intermediate in an enantiomerically pure form, resulting in a simple, concise, readily scalable, and asymmetric synthesis of (−)-antrocin (1 ). This strategy not only provides an efficient approach to (−)-antrocin (1 ) synthesis but can also be readily adopted for the syntheses of optically pure (+)-asperolide C (2 ) and (−)- trans -ozic acid (3 ) from the naturally abundant aromatic abietanes (+)-podocarpic acid (5 ) and (+)-dehydroabietic acid (6 ). The strategy presented here is an example of the use of naturally occurring aromatic abietanes as a chiral pool and offers an account of the asymmetric synthesis of terpenoids.